Blainvillea (Asteraceae-Heliantheae) is absent from China - Ren, Chen (Phytotaxa, 2017)
Blainvillea Cassini (1823: 493) (Asteraceae-Heliantheae), as recently circumscribed by Orchard (2012, 2015), is a pantropical genus comprising four species. Blainvillea calcicola Orchard (2012: 658) and B. cunninghamii (Candolle 1836: 540) Orchard (2012: 660) are endemic to Australia. Blainvillea gayana Cassini (1827: 90) is native to Africa and adventive in South America and Australia. Blainvillea acmella (Linnaeus 1753: 901) Philipson (in Koster & Philipson 1950: 350), the type species of the genus, is native to India and Sri Lanka, and adventive in northern Africa, Galápagos Islands, and Australia.